1999
DOI: 10.1021/bi990842e
|View full text |Cite
|
Sign up to set email alerts
|

Ser/Thr Protein Phosphatase Type 5 (PP5) Is a Negative Regulator of Glucocorticoid Receptor-Mediated Growth Arrest

Abstract: Ligand-induced glucocorticoid receptor (GR) activation has recently been linked to the inhibition of cell proliferation via the transcriptional induction of p21(WAF1/Cip1), which functions as a universal inhibitor of cyclin-dependent protein kinases. Herein, we identify a Ser/Thr protein phosphatase (PP5) that promotes cellular proliferation by inhibiting both glucocorticoid and p53-mediated signaling pathways leading to p21(WAF1/Cip1)-mediated growth arrest. The suppression of PP5 expression (1) markedly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
125
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 53 publications
11
125
1
3
Order By: Relevance
“…To gain insight into which of the cantharidin-sensitive PPases affect cell cycle progression and survival, we developed siRNA and antisense oligonucleotides capable of suppressing the expression of PP1g1 (20), PP5 (24,28,30), and, here, PP2Aa and PP2Ah. FACS analysis of propidium iodide -stained A549 cells treated with siRNA or antisense oligonucleotides targeting each of these PPase individually revealed that the suppression of PP5 expression results in a G 1 growth arrest with the concomitant increase in the expression of p21 Waf1/cip1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into which of the cantharidin-sensitive PPases affect cell cycle progression and survival, we developed siRNA and antisense oligonucleotides capable of suppressing the expression of PP1g1 (20), PP5 (24,28,30), and, here, PP2Aa and PP2Ah. FACS analysis of propidium iodide -stained A549 cells treated with siRNA or antisense oligonucleotides targeting each of these PPase individually revealed that the suppression of PP5 expression results in a G 1 growth arrest with the concomitant increase in the expression of p21 Waf1/cip1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…ISIS 15534 treatment also markedly increases the association of GR with its cognate DNA binding sequence and induces GR-transcriptional activity in the absence of glucocorticoids (18). When combined, ISIS 15534 and dexamethasone, a potent GR agonist, have an additive effect, with dexamethasone-mediated induction of GR reporter plasmid activity elevated to a level that is ϳ10 times greater than the maximal response obtainable in the presence of PP5 (18).Treatment with ISIS 15534 also suppresses the growth of some, but not all, human tumor cells (9,15,18). In p53 wildtype lung carcinoma cells, treatment with ISIS 15534 produces G 1 growth arrest, which occurs with a concomitant increase in the expression of the cyclin-dependent protein kinases inhibitor protein, p21 Waf1/Cip1 (15,18).…”
mentioning
confidence: 99%
“…Treatment with ISIS 15534 also suppresses the growth of some, but not all, human tumor cells (9,15,18). In p53 wildtype lung carcinoma cells, treatment with ISIS 15534 produces G 1 growth arrest, which occurs with a concomitant increase in the expression of the cyclin-dependent protein kinases inhibitor protein, p21 Waf1/Cip1 (15,18).…”
mentioning
confidence: 99%
See 2 more Smart Citations